Competitiveness of the Health Care - Delcheva, Evgenia (UNWE Yearbook, 2008)
In the research is analyzing theoretically and empirically the competitiveness of the health care in Bulgaria comparing EU through constructing of index for 2000-2004/2005 . In calculating the health care competitiveness index (HCCI) are used 21 indicators from the Data Base of WHO “Health For All”. The conclusions show, that the healthcare system in Bulgaria works better since 2000 when are started health reforms, as HCCI is increasing from 2.98 to 3.14. This is the lower level of competitiveness towards the EU member countries average (4,83-5,12), as well as EU-10 (3,39-3,97).